Etude variationelle d’un probl`eme de contact entre mat´eriaux th´ermo-´electro-visco´elastiques avec variable interne et endommagement - Messaoudi, Imane; Maˆamra, Maroua (university of eloued جامعة الوادي, 2023)
Akt 􀀀 ¨¶An 􀀀 AO ¯􀀀 T sm Tlyl t 􀀀 TF􀀀Cd 􀀀 w¡ r @m 􀀀 £@¡ dh 􀀀   ¤ Tyl 􀀀d 􀀀 T A 􀀀 ry t T zl 􀀀 Ty¶A rhkþ 􀀀¤ T§C􀀀r 􀀀 TysyFAt 􀀀 y 􀀀wql Aks§r y`R 􀀀 rf ¤ w ¤ Ab ³ Tlyl t 􀀀 TyRA§r 􀀀 AyW`Un this memoire we have study the problem of bilateral contact with Tresca’s friction for thermo-electro-viscoelastic. We conceder constitutive laws with internal state variable and damage,with arguments mathematicals and we have used this to prove the existence and uniqueness of a weak solution for the problem.m 􀀀 􀀀d tF􀀀 d ¤ ,C􀀀rR¯􀀀
mémoire masetre matimatuque
Keywords: CrS 􀀀 ,Tyl 􀀀d 􀀀 T A 􀀀 ry t ,TyVAWm 􀀀 T zl 􀀀 T§C􀀀r ¤rhkþ 􀀀 : Ty Atf Aml; hermo-electro-viscoelastics, internal state variable, damage,the bilateral contact, Tresca’s friction, weak solution, fixed point theorem.